Mental distress and podoconiosis in Northern Ethiopia: a comparative cross-sectional study - Mousley, Elizabeth (Int Health, 2015)
BACKGROUND: The stigma, deformity and disability related to most neglected tropical diseases may lead to poor mental health. We aimed to assess the comorbidity of podoconiosis and mental distress. METHODS: A comparative cross-sectional study was conducted in 2012, including 346 people with podoconiosis and 349 healthy neighbourhood controls. Symptoms of mental distress were assessed using the validated Amharic translation of the Kessler-10 scale (K10). A linear regression analysis was conducted to identify factors associated with mental distress. RESULTS: The mean K10 score was 15.92 (95% CI: 15.27 to 16.57) in people with podoconiosis and 14.49 (95% CI: 13.85 to 15.12) in controls (average K10 scores 1.43 points higher [95% CI: 0.52 to 2.34]). In multivariate linear regression of K10 scores, the difference remained significant when adjusted for gender, income, alcohol use, age, place of residence and family history of mental illness. In the adjusted model, people with podoconiosis had K10 scores 1.37 points higher than controls (95% CI: 0.64 to 2.18). Other variables were also associated with high K10 scores: women had K10 scores 1.41 points higher than men (95% CI: 0.63 to 2.18). Those with family history of mental illness had K10 scores 3.56 points higher than those without (95% CI: 0.55 to 6.56). CONCLUSIONS: This study documented a high burden of mental distress among people with podoconiosis compared with healthy controls. Taking this finding in the context of the high stigma and reduced quality of life, we recommend integration of psychosocial care into the current morbidity management of podoconiosis.